Modelo de gestión del talento humano orientado al sector lácteo del cantón Latacunga - Changoluisa Díaz, Lilian Mariana (2017)
The project consists of a proposal for a human talent management model for dairy companies in Latacunga canton, which through its use to improve the performance of the personnel, increasing the capacities and skills to obtain greater productivity. Firstly, the study has a theoretical and scientific support on the characteristics of human talent, personnel management processes and the different models of human talent management, among other aspects related to it. A quantitative approach was used to obtain real data for the study, the type of descriptive research was applied, and the deductive method was based on a general context to determine specific factors of Human Talent Management. On the other hand, as a data collection technique, a survey was carried out to 10 companies and each of the factors were diagnosed as: recruitment, human management and human development of both the workers and heads of human talent of the dairy companies.